Analisis Pengaruh Shift Kerja Terhadap Kecelakaan Kerja di Pabrik Kelapa Sawit : Literatur Review - Tasya Salsabillah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Occupational safety and health (K3) is safety related to machines, tools, materials and work processes, the foundation of the place and work environment, to instructions for doing work. The design used is Literature Review. The method of searching for article data sources was carried out through the Google Scholar database in the 2019-2023 period to retrieve relevant articles published in Indonesian. The purpose of making the five journals is to find out the relationship between work shifts and work accidents. Furthermore, these five designs use a cross-sectional design. According to Kuswadji (in Revalicha & Sami'an, 2013) work shifts are all arrangements for working hours, in lieu of or in addition to daytime work, as is usually done. A more operational definition of shift work is defined as work that is permanent, work with unusual working hours or work whose hours are always changing and also irregular.